2022
DOI: 10.1039/d2cp03664a
|View full text |Cite
|
Sign up to set email alerts
|

First principles study on thickness dependent structural and electronic properties unveiling the growth and stability of 2D layered II–VI semiconducting compounds

Abstract: By employing first principles density functional theory calculations on thickness dependent structural and electronic properties of (0001) surface slabs of wurtzite MX compounds, our study demonstrated the possibility of existence...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
3
6
0
Order By: Relevance
“…For 2D layers, three independent elastic constants, such as C 11 , C 22 , and C 66 , are calculated and reported in Table S6. These values for the 2d system are consistent with previous theoretical values. ,, For stable layers, it must obey the following mechanical stability according to Born’s criteria C 11 C 22 –C 12 2 > 0 and C 66 > 0. All 2D systems satisfy this criterion, indicating the mechanical stability of the system.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…For 2D layers, three independent elastic constants, such as C 11 , C 22 , and C 66 , are calculated and reported in Table S6. These values for the 2d system are consistent with previous theoretical values. ,, For stable layers, it must obey the following mechanical stability according to Born’s criteria C 11 C 22 –C 12 2 > 0 and C 66 > 0. All 2D systems satisfy this criterion, indicating the mechanical stability of the system.…”
Section: Resultssupporting
confidence: 89%
“…), graphene-like buckled 2D materials (silicene, germanene, arsenene, phosphorene, tinene, antimonene, etc. ), transition metal dichalcogenides (TMDs), and layered semiconductors that are being explored at the current moment. Recently groups II–IV, III–V, and IV–IV semiconductors have been drawing incredible research interest due to their promising electronic and optical properties. …”
Section: Introductionmentioning
confidence: 99%
“…We did perform calculations on a 12-layer sheet and showed that it is more stable in the wurtzite form and had a piezoelectric constant of 0.92 C/m 2 , which is 89% of the bulk value. Our findings agree with previous work, which showed that ZnO becomes buckled after 7- 16,17 or 10-15 layers. This is consistent with the structure preferring to be buckled, instead of graphitic, as it was for the thinner sheets.…”
Section: Piezoelectric Response and Buckling Of The Defect Nanosheetssupporting
confidence: 94%
“…Claeyssens et al showed using computational methods that ZnO nanosheets terminated by the polar (0001) and (0001̅) surfaces and having 18-layers or less flatten upon relaxation, becoming graphitic-like in structure up to 10-layers thick. Zhao et al and Devi et al also showed using density functional theory (DFT) calculations that ZnO sheets are flat up to a thickness of 7-layers. As a result of this flattening of the layers, the sheets lose their piezoelectric properties as the dipole moment from the buckled (0001) and (0001̅) surfaces no longer exists, meaning ultrathin ZnO nanosheets are not suitable for piezoelectric nanogenerators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation